1999
DOI: 10.1007/s004060050068
|View full text |Cite
|
Sign up to set email alerts
|

Differential therapy effects of psychoeducational psychotherapy for schizophrenic patients - results of a 2-year follow-up

Abstract: There is increasing evidence of the efficacy and effectiveness of psychosocial interventions in schizophrenic patients. However, little research has been done on differential therapy effects. In a prospective, randomized clinical trial we carried out psychoeducational medication management training, cognitive psychotherapy, and key-person counseling. The patients of the control group participated in structured free-time activities for control of therapeutic commitment. Data from a total of 156 schizophrenic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…Denn es liegen zu wenige Befunde vor [32,52], die Behandler bei differenziellen Indikationsentscheidungen unterstützen könnten.…”
Section: Implementierungshemmnisseunclassified
“…Denn es liegen zu wenige Befunde vor [32,52], die Behandler bei differenziellen Indikationsentscheidungen unterstützen könnten.…”
Section: Implementierungshemmnisseunclassified
“…Compared to a standard care control group, multiple family group treatment reduced both negative symptoms and the use of in-patient services [14,15] and has proved effective in both Hispanics and other ethnic groups with strong communitarian values [16]. Some studies show a reduction of caregiver burden after family intervention [17][18][19][20][21]; however, the multiple family trial by McDonell [5] failed to replicate these results, and other investigations found no improvement in coping, social support or psychological morbidity in relatives [22].…”
Section: Introductionmentioning
confidence: 99%
“…Prasko, K. Vrbova, K. Latalova, B. Mainerova Existing studies have generally shown that PEP has positive outcomes. For example, PEP was effective in reducing relapse 19,20 and improved patients' mental state, insight into their illness, and adherence to medication. Some studies, however, have suggested that it is unlikely that caregivers, particularly those of patients with a long history of illness, will change their views of patients after a short PEP intervention.…”
mentioning
confidence: 99%